Adulthood and mental illness in full inclusion - Claus Dieter Stobäus; Katiuscha Genro Bins; Juan José Mouriño Mosquera (Universidade Federal de Santa Maria (UFSM), 2012)
The article reweaves the information included in Bins' Master Dissertation discussions with his guide Stobäus and with Mosquera, centered in interfaces between Special Education and Full Inclusion, more in direction of the constitution of adult with mental deficiency and the relationship with learning, at the modality of teaching at Adolescent and Adult Education.